2022
DOI: 10.4103/japtr.japtr_313_21
|View full text |Cite
|
Sign up to set email alerts
|

Mode action prediction of catechin from Uncaria gambir Roxb. against UDP-N-acetylenolpyruvyl-glucosamine reductase (MurB enzyme) of Streptococcus mutans

Abstract: The prevalence of oral health problems in the global population is still high, especially dental caries, which is considered a multifactorial disease involving the role of bacteria, namely Streptococcus mutans. Gram-positive bacteria metabolize carbohydrates and sugars and convert them into lactic acid, causing dental caries. The peptidoglycan (PG) layer at the outer surface of the bacteria acts as protection. MurB enzyme is known for its contribution to PG biosynthesis. Gambir (Uncaria gambir Roxb.) is famous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…A majority of the phytochemical substances derived from gambir are categorized into the flavonoid, phenolic, and alkaloid groups [ 9 ]. Recent studies proved that the bioactive compounds of gambir have antibacterial, anticancer, anti-inflammation, as well as antifibrotic effects [ 10 , 11 , 12 , 13 ]. Desdiani et al [ 14 , 15 ] found using in vivo study that gambir has antifibrotic effect against lung fibrosis through inhibition of nuclear factor kappa-B (NF-κB) and transforming growth factor receptor (TGF-βR).…”
Section: Introductionmentioning
confidence: 99%
“…A majority of the phytochemical substances derived from gambir are categorized into the flavonoid, phenolic, and alkaloid groups [ 9 ]. Recent studies proved that the bioactive compounds of gambir have antibacterial, anticancer, anti-inflammation, as well as antifibrotic effects [ 10 , 11 , 12 , 13 ]. Desdiani et al [ 14 , 15 ] found using in vivo study that gambir has antifibrotic effect against lung fibrosis through inhibition of nuclear factor kappa-B (NF-κB) and transforming growth factor receptor (TGF-βR).…”
Section: Introductionmentioning
confidence: 99%